THE EFFECT OF VIDEO PUBLICATION ON PUBLIC INTEREST IN FOLLOWING SRIWIJAYA RANAU GRAN FONDO ACTIVITIES IN LAKE RANAU - Muhammad Ridho, Muhammad Ridho (Journal Of Social And Political Science, 2024)
The development of information technology is very rapid following the times where currently Digital Media is very important for disseminating information. The use of this fast-paced information technology is also used by Dinas Kebudayaan dan Pariwisata Provinsi Sumatera Selatan as an opportunity for a method of disseminating information in the form of activities carried out at Lake Ranau, so that researchers are interested in conducting research with the title "The Effect of Video Publication on Public Interest in Following Sriwijaya Ranau Gran Fondo Activities in Lake Ranau” by looking at the large number of social media users, especially Instagram, the researchers chose Instagram Followers @sriwijayaranaugranfondo, the general public, and participants in the Sriwijaya Ranau Gran Fondo activities as research objects. The theory used is S-O-R theory namely Stimulant (Message), Organism (Communication), Response (Effect) and the issue raised is is there any influence of video publication on public interest in participating in Sriwijaya Ranau Gran Fondo activities?. This study aims to determine whether there is an effect of video publication on public interest in participating in Sriwijaya Ranau Gran Fondo activities. This research uses quantitative methods. The data sources used were obtained through questionnaires, observations and interviews. As well as using descriptive analysis techniques, inferential analysis techniques and simple linear tests, the result is that the effect of video publication is 25.8% on public interest in participating in Sriwijaya Ranau Gran Fondo activities at Lake Ranau and the influence is positive